2020
DOI: 10.1097/j.pain.0000000000001908
|View full text |Cite|
|
Sign up to set email alerts
|

Imbalance of proresolving lipid mediators in persistent allodynia dissociated from signs of clinical arthritis

Abstract: Rheumatoid arthritis-associated pain is poorly managed, often persisting when joint inflammation is pharmacologically controlled. Comparably, in the mouse K/BxN serum-transfer model of inflammatory arthritis, hind paw nociceptive hypersensitivity occurs with ankle joint swelling (5 days after immunisation) persisting after swelling has resolved (25 days after immunisation). In this study, lipid mediator (LM) profiling of lumbar dorsal root ganglia (DRG), the site of sensory neuron cell bodies innervating the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 30 publications
(55 reference statements)
3
35
0
Order By: Relevance
“…MaR1, on the other hand, upon a single treatment, displays 5 days of analgesic effect when treatment is performed before stimulus with CFA and 3 days of analgesia when treatment is performed 24 h after the stimulus ( Fattori et al, 2019 ). In corroboration to our study, Allen and colleagues demonstrated that MaR1 presents 14 days of analgesia after repeated treatments ( Allen et al, 2020 ). These sets of data show that isolated SPMs demonstrate time-dependent and long-term efficacy even upon single treatment, which might be useful for the treatment of inflammatory diseases.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…MaR1, on the other hand, upon a single treatment, displays 5 days of analgesic effect when treatment is performed before stimulus with CFA and 3 days of analgesia when treatment is performed 24 h after the stimulus ( Fattori et al, 2019 ). In corroboration to our study, Allen and colleagues demonstrated that MaR1 presents 14 days of analgesia after repeated treatments ( Allen et al, 2020 ). These sets of data show that isolated SPMs demonstrate time-dependent and long-term efficacy even upon single treatment, which might be useful for the treatment of inflammatory diseases.…”
Section: Introductionsupporting
confidence: 92%
“…By this neuronal regulation, intrathecal treatment with MaR1 reduces the peripheral recruitment of inflammatory neutrophils and macrophages, reducing in addition to pain, peripheral inflammation (Fattori et al, 2019). In corroboration, Allen et al (2020) demonstrated that MaR1 also reduces calcium influx induced by capsaicin (TRPV1 agonist) in a GPCR-dependent manner and CGRP release. In another study, CIA-associate clinical score and cytokine profile were abrogated with MaR1 treatment (Jin et al, 2018).…”
Section: Dpa/dha-derived Spmsmentioning
confidence: 78%
See 2 more Smart Citations
“…In a mouse model of rheumatoid arthritis, persistent pain was not associated with joint swelling, but instead, was associated with decreased concentrations of MaR1. Furthermore, systemic MaR1 administration caused sustained reversal of mechanical hypersensitivity and reduced inflammatory macrophage numbers in DRG [78]. Given that macrophages are critical contributors to chronic pain pathogenesis by forming bidirectional communication with nociceptors [79], it remains important to identify whether endogenous macrophagederived maresins contribute to chronic pain resolution.…”
Section: Maresinsmentioning
confidence: 99%